Integrated malaria vector control strategies and their effectiveness in sub-Saharan Africa: a systematic review protocol for interventional studies - Diederick E Grobbee; Lihanimpo Djalogue; Marianne van der Sande; Patrice Ngangue; Gountante Kombate; Kamba Andre-Marie Soubeiga (BMJ Open)
Introduction Sub-Saharan Africa has the highest malaria burden in the world. Several vector control strategies are being implemented to reduce mosquito density and protect the most vulnerable populations, such as children under 5 and pregnant women. This systematic review is designed to assess the effectiveness of integrated vector control versus single vector control interventions on malaria incidence and prevalence to guide decisions on controlling malaria vectors in sub-Saharan Africa.Methods and analyses We will systematically retrieve published and grey literature from electronic databases and clinical trial registries. The Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines will guide us in applying a systematic approach to screening, reviewing and extracting data. An inclusion criterion will be used to independently assess full-text copies of potentially relevant articles by two review authors. Risk of bias will be assessed using the Cochrane Risk of Bias Tool V.2 for randomised controlled trials and the ROBINS-I (Risk Of Bias In Non-randomised Studies - of Interventions) tool for non-randomised intervention studies. A meta-analysis will be conducted based on studies that have reported a high level of evidence (risk ratios or ORs with 95% CIs). If substantial heterogeneity is encountered, subgroup analyses will be explored.Ethics and dissemination This review does not require ethical approval. The findings will be shared through open-access publications in peer-reviewed journals and presentations to stakeholders and international policymakers for malaria control.PROSPERO registration number CRD42024559088.